College Reconfiguration: Building Faculty Support - Maureen E Wilson; Dawn M. Shinew; Tracy L. Huziak-Clark; Deborah Wooldridge (Academic Chairpersons Conference Proceedings, 2023)
Following a year-long discussion, deliberation, and feedback process, faculty and staff in the College of Education and Human Development at Bowling Green State University voted overwhelmingly in support of reconfiguring from five schools and one department to three schools. We discuss our journey and outline the initial benefits, challenges, and lessons of this new configuration.
Keywords: Building consensus; leadership; resource management; organization; administration